Analisis Peran Indikator Kesehatan terhadap Pertumbuhan Ekonomi dan Peningkatan Indeks Pembangunan Manusia di Jawa Tengah - Daniswara, Rahma Hugo; Purnomo, Didit (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2025)
The human development index is designed to measure the extent to which the quality of human life has improved, taking into account education, health, and real per capita income. It helps in comparing national and regional human development performance. This study aims to identify the factors that influence the human development index of Central Java Province in 2023. Classical assumption tests for decision making using cross-section data. As shown by the research results, the Human Development Index is positively influenced by per capita income. Meanwhile, teachers, schools, and medical personnel have not yet been statistically able to influence the Human Development Index in Central Java Province during the 2023 period. Furthermore, regional development planners need to integrate public service quality indicators into human development evaluations to ensure that interventions are more targeted and directly impact the improvement of the Human Development Index.